Kadar Kolesterol Kuning Telur dan Daging Puyuh Jepang (Coturnix-coturnix japonica L.) setelah Pemberian Suplemen Serbuk Kunyit (Curcuma longa L.) - Putra, Sukarman Hadi Jaya; Saraswati, Tyas Rini; Isdadiyanto, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
This study aims to determine the effect of supplementation powder turmeric ( Curcuma longa ) before sexuality aging periods on cholesterol levels of eggs and meat Japanese quail ( Coturnix japonica coturnic ). Completely Randomized Design was applied in this research. Test animals used were 45 female Japanese quails were divided into three groups, P0 : Japanese quail are not given turmeric powder , P1 : Japanese quail given turmeric powder at a dose of 54 mg / individu / day , P2 : Japanese quail given turmeric powder at a dose of 108 mg / individu / day . The treatmant was repeated in 15 times. The treatment was given every day on 14th-44th day quail. The eggs were collected and analyzed the levels of cholesterol in the yolk , whereas cholesterol levels of meat taken after the Japanese quail was depicated . Data were analyzed using analysis of variance ( ANOVA ) followed by Duncan test with 95% significantly level ( Î± = 0.05). Analysis software is used Minitab software 16. Results showed that supplementationÂ of turmeric powder before sexuality aging periods on cholesterol levels Japanese quail eggs and meat a significant effect ( PË‚0.05 ) lower than the control. The results showed that doses up to 108 mg of turmeric powder / head / day can lower cholesterol Japanese quail eggs and meat . Â Keywords : Curcuma longa, Coturnix coturnix japonica, meat cholesterol, egg cholesterol